Scintillator material and its manufacturing method

The integration of carbon quantum dots with a graphite core into a polymer matrix addresses the inefficiencies of current beta scintillators by enhancing detection sensitivity and simplifying production, effectively detecting beta radiation.

JP2025514226APending Publication Date: 2025-05-02COMMISSARIAT A LENERGIE ATOMIQUE ET AUX ENERGIES ALTERNATIVES +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024563410
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-27
Filing Date
2023-04-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Current beta scintillators are complex to manufacture and require rare inorganic compounds, making them inefficient for detecting beta radiation effectively.

Method used

A scintillator material comprising carbon quantum dots with a graphite core dispersed in a polymer matrix, which emits UV radiation upon exposure to beta radiation, resulting in visible light emission.

Benefits of technology

The scintillator material achieves good detection sensitivity to beta radiation without the need for rare inorganic compounds, facilitating easier production and enhanced radiation protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514226000001_ABST
    Figure 2025514226000001_ABST
Patent Text Reader

Abstract

The present invention relates to a scintillator material comprising carbon quantum dots having a graphitic core and dispersed in a matrix, said material comprising aromatic units capable of emitting UV radiation in response to radiation exposure, in particular of the beta type, said UV radiation causing the carbon dots to luminesce and emit emitted light in the visible domain, and to a method for producing this scintillator material (3).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a scintillator capable of emitting photons under the influence of nuclear radiation, in particular beta radiation. [Background technology]

[0002] As first generation nuclear power plants begin to be decommissioned, detection of emissions in the form of waves, such as gamma or x-rays, or particles, such as beta radiation or neutrons, becomes an increasingly important challenge. There is good reason to believe that these needs will become even more acute as the number of decommissioning facilities increases.

[0003] In order to ensure the best possible radiation protection for decommissioning workers, in the future, scintillator materials with increasingly lower detection limits will be required. Although current gamma scintillators cover radiation protection requirements relatively well, feedback and experience of decommissioning personnel shows that there is still room for improvement when it comes to alpha or beta detection. This is essentially due to the low energies involved, which makes it difficult to detect these types of radiation.

[0004] Existing beta scintillators generally detect incident particles (β - or β + Inorganic crystals (CsI, GaO, CaF2) or plastic matrices (POPOP, benzene derivatives) are used as luminescent agents capable of converting photons into electrons (electrons or positrons in the case of

[0005] They are relatively complex to manufacture and, in the case of some inorganic crystals, such as those based on gallium, require the use of finite resources.

[0006] U.S. Patent Application Publication No. 2013 / 299742 discloses a material formed from a polymer matrix having dispersed therein a first phosphor capable of emitting radiation when irradiated and a second phosphor that absorbs the radiation and emits photons in the visible range.

[0007] US Patent Application Publication No. 2017 / 096600 discloses a material comprising graphene quantum dots dispersed in a polystyrene matrix, which is capable of emitting radiation in the visible range when exposed to ultraviolet radiation.

[0008] Finally, a paper by Zhan et al., published in Carbon Vol. 130 in 2018, entitled “A solvent-engineered molecule fusion strategy for rational synthesis of carbon quantum dots with multicolor bandgap fluorescence,” discloses a method for preparing carbon quantum dots. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] US Patent Application Publication No. 2013 / 299742 [Patent Document 2] US Patent Application Publication No. 2017 / 096600 [Non-patent literature]

[0010] [Non-Patent Document 1] Zhan et al., "A solvent-engineered molecular fusion strategy for rational synthesis of carbon quantum dots with multicolor bandgap fluorescence," Carbon, Vol. 130, 2018. Summary of the Invention [Problem to be solved by the invention]

[0011] There is therefore a need for scintillator materials that can be produced relatively easily, thereby avoiding the need to use rare inorganic compounds, if necessary, and that have good detection sensitivity for radiation, particularly beta radiation. [Means for solving the problem]

[0012] The present invention aims to meet this need, and does so by providing a scintillator material comprising carbon quantum dots having a graphitic core and dispersed in a matrix, said material comprising aromatic units capable of emitting UV radiation in response to radiation exposure, in particular beta radiation exposure, which UV radiation causes the carbon dots to luminesce and emit radiation in the visible range.

[0013] Such materials do not require the use of rare inorganic compounds and have good detection sensitivity to radiation, especially beta radiation.

[0014] According to another of its aspects, another subject of the invention is a method for detecting radiation originating from a radioactive source, in particular beta radiation, comprising exposing a scintillator material according to the invention to said radiation and detecting the emission of photons by said material in response to this exposure.

[0015] Another subject of the present invention is a radiation detector, in particular a beta radiation detector, comprising a scintillator material according to the invention, arranged so that it can be exposed to said radiation and equipped with at least one sensor for sensing photons emitted by said scintillator material in response to this exposure.

[0016] matrix The matrix may be thermoplastic or thermosetting. It may in particular be poured or injected in fluid form into a mold and then removed from the mold after cooling.

[0017] The matrix may be of any shape, in particular a polyhedron, for example a cube or parallelepiped, a solid or hollow cylinder, a cone, a toroid, among other possibilities, which may, if appropriate, be machined to the desired shape.

[0018] The matrix may also be present in the form of a layer that acts as a binder for the carbon dots.

[0019] The matrix is ​​preferably transparent, but may be translucent.

[0020] The matrix may be colorless and the material may have a brown color due to the presence of the carbon dots.

[0021] The matrix may also include one or more dyes.

[0022] This may incorporate light collecting elements or form a light guide where appropriate.

[0023] The matrix occupies any volume appropriate to the conditions of use, and its thickness ranges, for example, from 1 mm to 100 mm.

[0024] In particular when it is a polymer, the matrix polymer may have aromatic units as mentioned above.

[0025] The matrix may in particular be a styrene polymer, in particular polystyrene (PS), acrylonitrile-butadiene-styrene (ABS) or methyl methacrylate-butadiene-styrene (MBS), or may be chosen from aromatic polyethers (PAE), in particular poly(phenylene oxide) (PPO), polyvinyl toluene (PVT) or mixtures thereof. The matrix may in particular comprise or consist of polystyrene, which polymer makes it possible to achieve good results. The matrix may be a polymer. The polymer may be a homopolymer or a copolymer.

[0026] Aromatic Units The aromatic unit may be a phenyl ring, but any aromatic unit may be suitable that makes it possible to produce a UV emission under the action of the incident radiation to be detected and then a visible light emission by the carbon dot by transmission, in particular radiation transmission.

[0027] Thus, the aromatic unit can be, for example, a ring other than a phenyl ring.

[0028] The aromatic units may be present in a matrix, which may thus be a plastic material having aromatic units, as described above.

[0029] The aromatic units may, where appropriate, contain one or more heteroatoms and / or may be fused in the form of aromatic polycyclic compounds.

[0030] Carbon Dot Carbon dots are also known by the abbreviation "CD."

[0031] These are in the form of luminescent nanoparticles with a graphitic core, the size of which is less than 50 nm, preferably less than 10 nm.

[0032] The carbon dots are preferably hydrophobic, which may facilitate their dispersion in the polymeric precursor of the matrix.

[0033] In an exemplary embodiment, the carbon dots have trace amounts of nitrogen resulting from the synthesis method used. These trace amounts of nitrogen can contribute to improving the emission yield of the carbon dots because the nitrogen-containing groups act as exciton traps, resulting in an increase in the quantum yield of the carbon dots.

[0034] The carbon dots may have a non-zero nitrogen content, in particular an N1s atomic % content of 10-15%.

[0035] The carbon dots may have a non-zero oxygen content, in particular an O1s atomic % content of 15-20%.

[0036] The carbon dots may have a C1s atomic % content of 65-75%.

[0037] The content by mass of the carbon dots can be 0.01% to 0.5% with respect to the total mass of the scintillator material (carbon dots + matrix).

[0038] Synthesis method Carbon dots can be produced by decomposition (e.g. hydrothermal or microwave decomposition) of molecules used as precursors. These precursor molecules are preferably extracted from biomass, which constitutes an advantage in terms of the finite nature of the resources from which they can be produced.

[0039] The carbon dots result from a synthesis method using the decomposition of trinitropyrene, advantageously pre-dissolved in an organic solvent which may be toluene, dimethylformamide (DMF) or even better a toluene / DMF mixture.

[0040] The presence of DMF in the DMF / toluene mixture allows for a better yield by mass of carbon dots.

[0041] Method of preparation: Another subject of the invention is a method for preparing the scintillator material according to the invention, in which carbon dots are synthesized by implementing the previous synthesis method, in particular a synthesis method in which trinitropyrene previously dissolved in an organic solvent is decomposed, this organic solvent comprising a mixture of toluene and dimethylformamide (DMF).

[0042] As mentioned above, the matrix can be polymerized in the presence of the carbon dots. Alternatively, the matrix can be dissolved in a solution containing the carbon dots suspended in an organic solvent, which is then evaporated, for example in a mold having the desired shape.

[0043] It is thus possible to prepare a suspension of carbon dots in an organic solvent, in particular consisting of or containing toluene, dissolve the polystyrene in this solution, and then evaporate the solvent.

[0044] The invention will be better understood on reading the following detailed description of non-limiting exemplary embodiments thereof and on considering the accompanying drawings, in which: [Brief description of the drawings]

[0045] [Figure 1] FIG. 2 is a partial schematic diagram showing a setup for testing scintillator materials according to the present invention. [Diagram 2] FIG. 2 shows two original images obtained from a 90Sr source on a PS matrix only (left image) and on a scintillator material according to the invention having a PS matrix filled with 0.015% by weight of carbon dots (right image). [Diagram 3] FIG. 1 shows transmission electron micrographs (TEM) of carbon dots (images A and B) and a diffractogram of carbon dots (image C). [Figure 4] FIG. 1 illustrates the effect of the scintillator thickness on the radiated emission intensity. [Diagram 5]FIG. 1 shows the effect of carbon dot concentration on radiated emission intensity. [Figure 6] FIG. 13 shows the effect of the presence of carbon dots in a PS matrix in the case of a 90Sr source (left image) and a 14C source (right image). [Figure 7] FIG. 1 shows the XPS of the carbon dots used for scintillation (left) and the associated content of carbon (C), nitrogen (N), and oxygen (O). [Figure 8] FIG. 1 shows the deconvolution of XPS spectra associated with carbon dots used for scintillation and the identification of functional groups present in the carbon dots using fitted lines. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] FIG. 1 shows an installation 1 (also called test bench) for testing a scintillator material 3 according to the invention, comprising a radioactive source 2 arranged on one side of the scintillator material 3 and a camera 4 arranged on the opposite side, the entire assembly being placed in a black box 5 for observing the scintillator material 3.

[0047] The camera 4 is equipped with a photodetector that makes it possible to count photons within a spectral range that covers the UV-visible range of light (180-900 nm).

[0048] The radioactive source 2 used in the test delivers, for example, an energy of 546 keV and has a radioactivity of 12 kBq. 90 Sr source, delivering an energy of 156 keV and having an activity of 33 kBq 14 C sources are pure beta emitters.

[0049] The scintillator material 3 may be in the form of a solid block of parallelepiped or cylindrical shape, although any shape is possible.

[0050] The scintillator material 3 can be fabricated in two steps.

[0051] First, the carbon dots are synthesized in the form of a powder. Second, this powder is dispersed in a liquid monomer in the presence of a polymerization initiator. After the waiting time required for the polymerization of the monomer, the carbon dots are fixed in a transparent plastic matrix, for example polystyrene.

[0052] It is also possible to avoid the waiting times associated with the polymerization of the monomers. In this case, it is necessary to prepare a suspension of carbon dots in toluene beforehand. Then, 5 g of polystyrene are dissolved in 10 ml of this suspension. Finally, the mixture is placed in a mold with the desired shape and left to stand, allowing the toluene to evaporate. After 48 hours, a polystyrene scintillator filled with carbon dots is obtained.

[0053] Carbon dots have the following formula:

[0054] [ka]

[0055] It can be synthesized from trinitropyrene having the formula:

[0056] A solution of trinitropyrene is prepared, for example, in dimethylformamide (DMF) at a concentration of 10 mg / ml. This solution can then be placed in a microwave oven at 200° C. for 1 hour or in an autoclave at 200° C. for 8 hours. A purplish black solution is obtained at the end of the reaction. This solution is slowly evaporated, for example, at 70° C. for 72 hours. After the evaporation step, a black powder is collected. This black powder may be redispersed in 5 ml of ethanol. These 5 ml are then dialyzed, for example, for 24 hours, in a specific 1 kDa tube to remove unreacted species. The solution of ethanol containing the purified carbon dots is then evaporated, for example, at 70° C. overnight.

[0057] After this final evaporation step, a black powder of purified carbon dots is obtained, which can then be used to prepare scintillator materials.

[0058] The synthesis is preferably carried out in DMF, since it is preferable to obtain hydrophobic carbon dots that are easier to subsequently disperse in the monomer that serves as a precursor for the transparent plastic matrix.

[0059] Figure 3 shows TEM images and diffractograms for the carbon dots thus prepared. The size of the carbon dots is polydisperse, ranging from a few nm to 50 nm (images A and B). XRD analysis (image C) shows a conventional diffractogram typically obtained for carbon dots, with a broad peak at around 25° to the plane (002) of the graphitic core of the carbon dots.

[0060] To manufacture a block of scintillator material 3, for example, a mass of 5 mg to 15 mg of carbon dots is taken and then dispersed in 20 ml of styrene while stirring. A mass of, for example, 0 to 20 mg of a polymerization initiator, such as benzoyl peroxide, is then added. The viscous liquid is then placed in a mold intended to give the scintillator material its shape and left to mature, for example at a temperature of 70° C. to 110° C., for a period of, for example, 5 to 25 days.

[0061] The setup of FIG. 1 makes it possible to test the radioluminescent properties of the scintillator material 3 according to the invention thus obtained.

[0062] A radioactive source 2 illuminates a scintillator material 3 in an excited energy state. During its de-excitation, the scintillator material 3 emits photons, which are captured by a detector in a camera 4. The signal collected by the camera in the form of an image is then analyzed by a computer 7 running image processing software to obtain curves that make it possible to compare the effectiveness of each scintillator material.

[0063] Figure 2 shows the results of a radioluminescence test carried out using the test bench of Figure 1. It can be seen that the sample containing carbon dots (right image) emits more photons than the PS-only matrix (left image). Thus, there is clearly a carbon dot effect involved in the radioluminescence mechanism of the scintillator material according to the invention.

[0064] Figure 6 shows that for the same exposure time, 90 The Sr source (left image) 14 This causes the emission of more photons in the visible range of light than the C source (right image), indicating that the strength of the detected signal can depend on the energy of the radiation in question.

[0065] 5 shows the effect of the concentration of carbon dots in a matrix on the radiative emission intensity of a scintillator material according to the present invention, in this example the scintillator material is 9 mm thick and 13 mm long, with concentrations of 0.045% by weight (higher intensity), 0.027% by weight (medium intensity), and 0.015% by weight (lower intensity), respectively.

[0066] Figure 4 shows 90 The effect of the thickness of the scintillator material placed in the path of the incident radiation on the radiated emission intensity due to Sr is shown. It can be seen that the radiated emission intensity is actually due to the presence of the scintillator material, and therefore the presence of the carbon dots in this material, since the radiated emission intensity increases with increasing thickness of the scintillator material. In this figure, for the same concentration of carbon dots at 0.027% by mass, the maximum intensity is obtained for a thickness of 9 mm and the minimum intensity is obtained for a thickness of 2 mm.

[0067] Figure 7 shows the XPS spectra of the carbon dots and their calculated content of carbon (69.5%), nitrogen (12.4%) and oxygen (18.1%). Deconvolution of the peaks of the XPS spectrum shown in Figure 8 makes it possible to identify the different groups present on the surface of the carbon dots.

[0068] Of course, the invention is not limited to the exemplary embodiments described above.

[0069] For example, the scintillator material may be used to detect radiation other than beta radiation, such as alpha or gamma radiation.

[0070] The matrix may be formed using other polymers and the aromatic units may be present in other forms.

[0071] The scintillator material may be combined with other scintillator materials for the purpose of detecting other radiation, for example neutron radiation. [Explanation of symbols]

[0072] 1 equipment 2 Radioactive sources 3 Scintillator materials 4. Camera 5. Black Box 7. Computers

Claims

1. A scintillator material (3) comprising carbon quantum dots having a graphite core and a non-zero nitrogen content, the dots being dispersed in a matrix, the material comprising aromatic units capable of emitting UV radiation in response to radiation exposure, in particular beta radiation exposure, the UV radiation causing the carbon dots to luminesce and emit radiation in the visible range.

2. The material of claim 1 , wherein the matrix is ​​a polymer, and the polymer of the matrix comprises the aromatic units.

3. The material of claim 2 , wherein the aromatic unit is a phenyl ring.

4. 4. The material according to claim 2 or 3, wherein the matrix comprises or consists of polystyrene.

5. The material of any one of claims 1 to 4, wherein the carbon dots have an N1s atomic % content of 10-15%.

6. The material according to any one of claims 1 to 5, wherein the carbon dots have a non-zero oxygen content, in particular an O1s atomic % content of 15-20%.

7. 7. The material of claim 1, wherein the carbon dots have a C1s atomic % content of 65-75%.

8. The material according to any one of claims 1 to 7, wherein the content by mass of the carbon dots is between 0.01% and 0.5% relative to the mass of the material.

9. The material of claim 1 , wherein the carbon dots are produced by decomposition of trinitropyrene.

10. 10. The material of claim 1, wherein the carbon dots are hydrophobic.

11. 11. A method for detecting radiation originating from a radioactive source, in particular beta radiation, comprising exposing a scintillator material according to any one of claims 1 to 10 to said radiation and detecting the emission of photons by said material in response to said exposure.

12. A radiation detector, in particular a beta radiation detector, comprising a scintillator material (3) according to any one of claims 1 to 10, arranged to be exposed to said radiation and having at least one sensor (4) for sensing photons emitted by the scintillator material in response to said exposure.

13. A method for preparing carbon dots, particularly intended for its use for producing a scintillator material as claimed in any one of claims 1 to 10, comprising decomposing trinitropyrene previously dissolved in an organic solvent, the organic solvent comprising a mixture of toluene and dimethylformamide (DMF).

14. A method for producing a scintillator material according to any one of claims 1 to 13, comprising synthesizing the carbon dots by carrying out the method according to claim 13.

Citation Information

Patent Citations

  • Solid organic scintillator doped by one or more chemical elements

    US20130299742A1

  • Graphene quantum dot-polymer composites and methods of making the same

    US20170096600A1